Mechatronics book series: robotics and automation - Akmeliawati, Rini; Sediono, Wahju; Alang Md Rashid, Nahrul Khair (IIUM Press, 2011)
This book is part of the Mechatronics Book Series that contains contributions on Robotics and Automation. The book contains chapters, which can be divided into two main parts; majority of chapters related to Robotics and the remaining seven chapters on Automation. In Robotics, design and development of various types of robots and robot parts, such as biped robot, humanoid robotic hand, head and arm, fish robot, cleaning robot, snake robot and hexapod robot, are presented. Robots for numerous applications, such as robots for upper limb rehabilitation, mobile robot for tube inspection, person following robot and goal finding robot, are designed and discussed. In each of robotic related chapter, types of sensors, actuators and system integration are well studied. In Automation, applications of supervisory control and data acquisition (SCADA) for pipe monitoring, water treatment, distribution system are presented. Automations in landmark generation for automatic mapping system, food storage system, and that in hazardous environment are also investigated. The book provides states of the art which will be useful for graduate students, researchers and engineers as a practical guide to implementation of Mechatronics in Robotics and Automation, particularly in robot design and development, and automation applications.